SPNS2 promotes the malignancy of colorectal cancer cells via regulating Akt and ERK pathway. (30th June 2019) - Gu, Xinyue; Jiang, Yang; Xue, Weinan; Song, Chengxin; Wang, Yangyang; Liu, Yanlong; Cui, Binbin
Abstract: Colorectal cancer (CRC) is a prevalent malignant tumour that causes considerable cancer‐related deaths globally. The sphingolipid transporter 2 (SPNS2), a sphingosine‐1‐phosphate (S1P) transporter, modulates multiple biological events including malignancy of cancer cells. In this study, the effects of SPNS2 on CRC progression were studied. We found that SPNS2 expression was significantly upregulated in CRC tissues compared to that in adjacent non‐tumour tissues. To assess the role of SPNS2 in CRC cells, we performed loss‐ and gain‐of‐function experiments in SW480 and HCT116 cells, respectively. The results demonstrated that SPNS2 promoted proliferation, migration and invasion, and inhibited apoptosis in CRC cells. Additionally, SPNS2 enhanced the release of intracellular S1P, and increased S1P receptor 1 (S1PR1) and S1PR3 expression. Moreover, SPNS2 activated the Akt and ERK pathways, and the biological behaviours of SPNS2 were attenuated by Akt or ERK inhibitor in HCT116 cells. In conclusion, our results demonstrated that SPNS2 promoted proliferation, migration and invasion, and inhibited apoptosis by regulating S1P/S1PR1/3 axis and activating Akt and ERK pathway in CRC cells.